Eksistensi Pondok Pesantren Salafiah Sa’adatuddaren di Era Modernisasi Pendidikan - Marwazi Marwazi; Abul Khoir (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2019)
In the modern era, competition in various lines of life is getting tougher, education has not escaped the demands of the modern era so that the term education modernization appears. Modernization of education wants a learning model with sophisticated technology, focusing its expertise to be able to talk a lot in the field of work. Related to this, Salafiah Islamic Boarding School which is identical with its old, old education system is considered to be no longer relevant to the development of the times demanded to be able to maintain its existence with renewal efforts which certainly does not leave its characteristics as Salafiah Islamic Boarding School. This research took place in the Salafiah Sa'a Islamic Boarding School, Seberang, Jambi City. This study aims to determine the existence of the Salafiah Islamic Boarding School in the modernization era of education, what constraints faced by the Salafiah Islamic Boarding School in the modernization era of education, and what efforts have been made by the Islamic Boarding School in the era of education. education. The method used in this research is qualitative. The types of data used are primary and secondary. The data source is the informant associated with the existence of the Salafiah Sa' adatuddaren Islamic Boarding School in the era of education modernization, which was collected through observation, interviews and documentation. The findings of this study indicate that in the current era of education modernization, the Salafiah Islamic Boarding School 'adatuddaren still exists even though the number has indeed decreased but not too significantly. The efforts made by the Salafiah Sa'a adatuddaren Islamic Boarding School to maintain its existence in the era of education modernization are good enough, only it needs to be continuously evaluated by looking at existing obstacles, and the demands and demands of the times both in the world of education and employment.